2021
DOI: 10.1158/2159-8290.cd-20-1274
|View full text |Cite
|
Sign up to set email alerts
|

Nongenetic Evolution Drives Lung Adenocarcinoma Spatial Heterogeneity and Progression

Abstract: Cancer evolution determines molecular and morphological intra-tumor heterogeneity and challenges the design of effective treatments. In lung adenocarcinoma, disease progression and prognosis are associated with the appearance of morphologically diverse tumor regions, termed histologic patterns. However, the link between molecular and histological features remains elusive. Here, we generated multi-omics and spatially resolved molecular profiles of histologic patterns from primary lung adenocarcinoma, which we i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 110 publications
6
80
0
Order By: Relevance
“…With these key advantages, GeoMx allows researchers to achieve a wide spectrum of spatially resolved transcriptomic and proteomic characterizations of breast cancer samples [4,35,[45][46][47]. Furthermore, the GeoMx spatial profiling is applicable for other tumor types, such as melanoma, lung, prostate, or liver cancers, characterized by high clinical and histological heterogeneity [48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Geomx Digital Spatial Profiler (Dsp) For Spatially Resolved Biologymentioning
confidence: 99%
“…With these key advantages, GeoMx allows researchers to achieve a wide spectrum of spatially resolved transcriptomic and proteomic characterizations of breast cancer samples [4,35,[45][46][47]. Furthermore, the GeoMx spatial profiling is applicable for other tumor types, such as melanoma, lung, prostate, or liver cancers, characterized by high clinical and histological heterogeneity [48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Geomx Digital Spatial Profiler (Dsp) For Spatially Resolved Biologymentioning
confidence: 99%
“…LUAD progression is driven by epigenetic changes that lead to increased plasticity relative to normal cells of origin, which ultimately enables cancer cells to undergo profound changes in cell identity that enhance malignant potential [1][2][3][5][6][7][8][9][10][11][12] . Here we show that FoxA1/2 regulate critical aspects of lineage plasticity and infidelity, coordinately driving multiple cell identity programs that are essential for LUAD progression (Figure 7H, top).…”
Section: Discussionmentioning
confidence: 99%
“…In lung adenocarcinomas, the tumor tissue architecture is often heterogeneous, especially in early-stage diseases, and it gives rise to histologic patterns recognized by histopathology analyses (Travis et al, 2015). Recent evidence from histopathology-guided multiregional sampling has ll OPEN ACCESS iScience 24, 102403, May 21, 2021 shown that this heterogeneity does not correspond to emergence of specific genetic variants, but it rather reflects epigenetic and transcriptional reprogramming associated with cell de-differentiation and increased proliferation (Tavernari et al, 2021). Additional examples include reprogramming to a progenitor state of luminal breast cancer cells (Domenici et al, 2019;Poli et al, 2018), intermixing and transition between differentiated and progenitor states in melanoma (Cheli et al, 2011;Roesch et al, 2010), epithelial plasticity in pancreatic cancer (Genovese et al, 2017;Reichert et al, 2018), de-differentiation trajectories in glioblastoma (Gallo et al, 2015), or lineage reprogramming from adeno to neuroendocrine carcinoma in prostate and lung cancer (Park et al, 2018), which, similarly to EMT, shows evidence of a continuum of states along which individual tumors may transition and evolve (Ireland et al, 2020).…”
Section: The Plastic Identity Of Cancer Cellsmentioning
confidence: 99%